IKLIM MIKRO HUTAN BERDASARKAN NORMALIZEDDIFFERENCEVEGETATION INDEX (NDVI) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS(KHDTK) UNIVERSITAS LAMBUNG MANGKURATPROVINSI KALIMANTAN SELATAN - Tri Wahyuni; Ahmad Jauhari; Adistina Fitriani (Jurnal Sylva Scienteae, 2020)
The purpose in this research to analyze the microclimate using a comfort index based on the canopy density results from NDVI analysis in KHDTKLambungMangkurat University. The research from February-April 2018. The research location was purposive sampling the results of NDVI analysis using QGIS, microclimate parameters (temperature, humidity and light intensity) with a field survey using a circular plot with a radius of 17.84 m. Data analysis based on comfort index (THI) from Setyowati (2008). The percentage of canopy density is very rare at 55.69% with an average light intensity of 3242.20 lux. The percentage of canopy density is rarely as much as 86.99% with an average light intensity of 1222.8 lux. The percentage of medium canopy density was 88.93% with an average light intensity of 1118.3 lux. The comfort index shows that in the morning THI is very rare, rare and moderate density of 26.36; 25.69 and 26.03 fall into the comfortable category. THI is very rare, rare and moderate density of 30.24; 29.67 and 29.68 fall into the uncomfortable category during the day. THI is very rare, rare and moderate density of 28.28; 28.00 and 27.94 fall into the category of partially uncomfortable in the afternoon.Keywords: Micro Climate; Normalized Difference Vegetation Index (NDVI); TemperaturHumadity Index (THI)